The new in research of hematological features of uteroplacental blood flow at pathology of thyroid gland in mother - T V Pavlova; E S Malyutina; V A Petruhin (IP Berlin A.V., 2014)
The research of macro - and microelements in uterus, placenta and umbilical cord at the pregnancy on background of pathology of thyroid gland of various genesis (euthyroid condition, diffuse toxic goiter, hypothyreosis) was conducted with help of electron microscopy with usage of detector for registration of spectrums. Recieved data at this pathology testifies about authentic decline of oxygen and other elements in umbilical cord, placenta and uterus, what is necessary to consider at correction of uteroplacental exchange with aim to decreasing of risks of obstetric and perinatal complications.